Wortlautgrenze und Wörterbuch - Christensen, Ralph; Kübbeler, Christian (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2011)
Proper interpretation criteria exist in many text-related disciplines. Jurists are even constitutionally bound to accurate statutory interpretation. This principle is achieved thanks to the semantic boundaries criteria (Wortlautgrenze) inherent in the wording of a given text. On the one hand, reliance solely on dictionaries to identify this boundary would result in overevaluation of their potential. On the other hand, if one solely depends on these semantic boundaries without consulting a dictionary at all, their potential remains undervalued. The performance of dictionaries can only be judged correctly if we realize that these semantic boundaries do not lie in the books, but in conflicts.